Assume that $X$ and $Y$ are two arbitrary non-negative random variables. Is the following inequality true for $1\leq\alpha\leq 2$?

\begin{align} \left(\mathbb{E}\left[X^\alpha\right]-\mathbb{E}\left[X\right]^\alpha\right)^{\frac{1}{\alpha}}+\left(\mathbb{E}\left[Y^\alpha\right]-\mathbb{E}\left[Y\right]^\alpha\right)^{\frac{1}{\alpha}}\geq \left(\mathbb{E}\left[(X+Y)^\alpha\right]-\left(\mathbb{E}\left[X+Y\right]\right)^\alpha\right)^{\frac{1}{\alpha}} \end{align}

  • $\begingroup$ you mean that $X,Y$ take non-negative real values? $\endgroup$ Feb 6, 2018 at 19:01
  • $\begingroup$ Yes, $X$ and $Y$ take non-negative real values. $\endgroup$
    – Math_Y
    Feb 6, 2018 at 19:23
  • $\begingroup$ I have restored the original condition $\alpha\ge1$ on $\alpha$. $\endgroup$ Feb 6, 2018 at 19:54

1 Answer 1


The answer to this question is yes.

Indeed, let $a:=\alpha$, and suppose $1\le a\le2$. Without loss of generality (wlog), $1<a\le2$, $EX^a<\infty$, and $Y$ takes only values in a fixed finite set $S\subset[0,\infty)$. The inequality in question is equivalent to the following: \begin{equation} h(t):=h_{X,Y}(t):=[E(X+tY)^a-E^a(X+tY)]^{1/a}-(EX^a-E^a X)^{1/a}-t(EY^a-E^a Y)^{1/a}\le0 \end{equation} for all $t\ge0$, and hence to the condition $h'(0)\le0$ (because $\frac d{dt}h_{X,Y}(t)=\frac d{du}h_{X+tY,Y}(u)|_{u=0}$). In turn, the condition $h'(0)\le0$ can be rewritten as \begin{equation} (EX^{a-1}Y-E^{a-1}X\,EY)(EX^a-E^a X)^{1/a-1}\le(EY^a-E^a Y)^{1/a}, \end{equation} and then in this H\"older-like form: \begin{equation} F(\mu):=(EX^{a-1}Y-E^{a-1}X\,EY)_+^a-(EX^a-E^a X)^{a-1}(EY^a-E^a Y)\le0, \end{equation} where $u_+^a:=\max(0,u)^a$ and $\mu=\mu_Y$ is the probability distribution of $Y$, with the random variable (r.v.) $X$ considered fixed.

Obviously, the function $F$ is convex on the simplex $M_S$ of all probability distributions $\mu_Y$ on $S$. So, the maximum of $F$ on $M_S$ is attained when $\mu$ is a Dirac measure -- that is, when the r.v. $Y$ is a nonnegative constant $c$, so that
$F(\mu)=c^a(EX^{a-1}-E^{a-1}X)_+^a=0$, because $1<a\le2$ and hence $EX^{a-1}\le E^{a-1}X$. So, the maximum of $F$ on the simplex $M_S$ is $0$, which completes the proof for the case $1\le a\le2$.

Moreover, following the lines of the above proof, it should be clear that the inequality in question fails to hold in general for any $a>2$. Indeed, then, for instance, $F(\mu)=\frac12-(\frac12)^{a-1}>0$ if $Y=1$ and $P(X=0)=P(X=1)=1/2$, which implies $h'(0)>0$, which implies $h(t)>0$ for small enough $t>0$.

  • $\begingroup$ Sorry, I have forgotten to mention that $\alpha\leq 2$. $\endgroup$
    – Math_Y
    Feb 6, 2018 at 19:56
  • 2
    $\begingroup$ Then you should probably ask that as a separate question, with that additional condition. $\endgroup$ Feb 6, 2018 at 19:57
  • $\begingroup$ If $1\le\alpha\le2$, then the inequality holds. I have now added the corresponding proof. $\endgroup$ Feb 6, 2018 at 21:19
  • $\begingroup$ This proof is mistaken, since $EX^{a-1}Y$ and hence $F(\mu)$ are not actually functions of $\mu$, even with $X$ fixed. A correct (but much involved) proof can be found at arxiv.org/abs/1807.11108 . $\endgroup$ Aug 1, 2018 at 14:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.